Optimization of industrial symbiosis in coffee-based eco-industrial park design - N. Laili; T. Djatna; N.S. Indrasti; M. Yani (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The coffee agroindustry in Indonesia plays a significant economic role as the third largest coffee producer worldwide. Despite the high economic contribution, the coffee agroindustry also raises environmental issues along its supply chain. Coffee solid waste constitutes biomass containing useful compounds promising as raw materials for added-value products through the implementation of industrial symbiosis. Eco-industrial parks create value through industrial symbiosis, emphasizing the principle of a closed-loop production system, simultaneously decreasing the use of raw materials and waste. This study aimed to analyze and develop a coffee-based eco-industrial park design via a systems engineering approach and optimization of industrial symbiosis in closed-loop coffee production.METHODS: This study employed a case study in the Ketakasi coffee-producing center in Jember, Indonesia. Data collection was conducted through field observation and a series of in-depth interviews. The development of eco-industrial park design followed a systems engineering methodology, as demonstrated through the utilization of Business Process Model and Notation. Subsequently, the optimization of industrial symbiosis within eco-industrial parks was realized using a mixed-integer linear programming mathematical model.FINDINGS: The eco-industrial park design presents the actors, internal business processes, material and data exchanges, various actors’ interdependence and critical roles in material exchanges, and value creation processes using valorization within the eco-industrial park. The role of the Ketakasi cooperative as a facilitator of material exchange and manager of the eco-industrial park is pivotal. The utilization of data integration enhances the transparency and efficiency of information exchange among eco-industrial park participants, promoting predictability and reliability in material exchange. The application of the mixed-integer linear programming optimization model has provided a structured approach to maximizing the value creation within the eco-industrial park through the valorization of 72.3 percent of coffee pulp and 68.5 percent of spent coffee grounds into cellulase enzymes and ultraviolet shields.CONCLUSION: This paper presents a structured framework for efficiently managing material exchange processes within an eco-industrial park, contributing to environmental sustainability and economic value creation. This study contributes to the knowledge gap in the literature by developing an inclusive eco-industrial park design that facilitates the optimization of the value creation process through valorization technology. This study also adds to sustainable agriculture management literature through a coffee-based eco-industrial park design.